The General Data Protection Regulation - a practical guide for trade unionists - Buffard, Sally (London, 2018)
"The General Data Protection Regulation (GDPR) updates data protection laws to reflect rapid advances in technology and the growth of the digital economy. The new law introduces important changes to how personal data can be used and organisations will have new responsibilities and duties to fulfil. This LRD booklet explains the main provisions of the GDPR that are relevant to trade unions, setting out the legal framework and providing step-by-step guidance for trade union reps on how to comply with the data protection laws."